2020
DOI: 10.1002/adfm.202008061
|View full text |Cite
|
Sign up to set email alerts
|

Sono/Photodynamic Nanomedicine‐Elicited Cancer Immunotherapy

Abstract: Immunotherapy (e.g., cancer vaccines and checkpoint blockades), harnessing the host immune system to recognize and eradicate tumors, has emerged as one of the most potent cancer therapies. The clinical applications of cancer immunotherapies, however, have been limited by their low response rates and immune‐related adverse effects. In recent years, sono/photodynamic nanomedicines (SPNs) have received increasing attention for cancer therapy since they have been reported to mediate enhanced immunotherapy by gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 264 publications
0
45
0
Order By: Relevance
“…For this reason, SDT and PDT synergistic treatment strategy may offer a more effective treatment than monotherapy ( Abrahamse and Hamblin, 2016 ). In addition, sono/photodynamic combined therapy approaches were reported to improve the efficacy of various immunotherapeutic strategies used in tumors ( Shi et al, 2019 ; Li et al, 2020b ). PDT can trigger immunogenic cell death, which stimulates immune responses against dead cell antigens ( Green et al, 2009 ; Kroemer et al, 2013 ; Ng et al, 2018 ).…”
Section: Novel Approaches To Improve Outcomementioning
confidence: 99%
“…For this reason, SDT and PDT synergistic treatment strategy may offer a more effective treatment than monotherapy ( Abrahamse and Hamblin, 2016 ). In addition, sono/photodynamic combined therapy approaches were reported to improve the efficacy of various immunotherapeutic strategies used in tumors ( Shi et al, 2019 ; Li et al, 2020b ). PDT can trigger immunogenic cell death, which stimulates immune responses against dead cell antigens ( Green et al, 2009 ; Kroemer et al, 2013 ; Ng et al, 2018 ).…”
Section: Novel Approaches To Improve Outcomementioning
confidence: 99%
“…Using other photosensitizers other than hypericin failed to induce the exposure of calreticulin on cell surface ( Garg et al, 2012 ), suggesting the necessity of choosing suitable photosensitizers or choosing suitable drug carriers to afford enhanced affinity to ER. 2) Sonodynamic therapy is similar with PDT but employs ultrasound as the energy source ( Li et al, 2021 ), and has been reported to elicit ICD. For instance, a nanocomposite loaded with chlorin e6 (as a sonosensitizer) induced ICD via receptor-interacting protein kinase 3–dependent cell necroptosis ( Um et al, 2020 ).…”
Section: Interlacing Roles Of Ros In Immunotherapymentioning
confidence: 99%
“…13 Sonodynamic therapy (SDT), derived from PDT, that utilizes ultrasound (US) to activate the sonosensitizer to produce ROS possesses deep tissue penetration, provides a more effective and safer strategy for the treatment of deep tumors, showing unique advantages and great potential in anti-tumor immunotherapy. [14][15][16] Page 2 of 32 CCS Chemistry 6 sonosensitiser-encapsulated dot aqueous solution, followed by purification by 5000 rpm ultrafiltration for 10 min and filtration using a 0.45 μm syringe driven filter.…”
Section: Introductionmentioning
confidence: 99%